A comparison between methods of measuring postrual stability: force plates versus accelerometers - Seimetz, Christina; Tan, Danica; Katayama, Riemann; Lockhart, Thurmon (Biomedical sciences instrumentation, 2012)
Several methods exist for the assessment of balance. In the clinical setting, they are often assessed through qualitative tests. In the laboratory, instrumentation can quantitatively and more accurately measure balance. To date, force platforms remain one of the most commonly used tools in balance assessment. They are, however, costly and cumbersome, making them impractical in clinical settings and field studies. Utilization of accelerometers in balance assessment has been studied but has not yet become a laboratory standard due to the unknown accuracy of this method. If proven accurate, the use of accelerometers in laboratory and clinical environments would be ideal because they are inexpensive, noninvasive, and easy to transport. The purpose of this study was to compare the use of accelerometers as an inclinometer to the use of a force platform in the assessment of postural stability. A triaxial accelerometer was placed on the trunk of five subjects. The subjects stood barefoot on a force platform under various conditions which affect balance: all sensory systems intact; impaired visual feedback; impaired proprioceptive feedback; and impaired visual and proprioceptive feedback. During each trial, trunk acceleration and ground reaction forces and moments were collected. Force plate data was used to plot the path of the center of pressure and acceleration data was used to plot a projected path of the trunk acceleration. Behavioral similarities were seen in both methods of balance assessment. Therefore, balance assessment via accelerometers is feasible. This method does, however, require further investigation.